Recent advances in vaccine delivery - Soni Khyati J., Patel Rakesh P., Asari Vaishnavi M., Prajapati Bhupendra G (Journal of Applied Pharmaceutical Science)
Although currently available vaccines represent an outstanding success story in past few years and it is clear that improvements in vaccine delivery and introduction of new vaccines are required. Vaccine delivery improvements may include the use of novel routes of delivery including intradermal, intranasal, tanscutaneous, and needle free delivery. Intradermal delivery includes delivery of vaccine to the dermis or epidermis for enhancement of immunogenicity. Needle free delivery present lowest risk of needle stick injury and transmission of blood borne pathogen through needle and increase compliance. This review represents the different delivery system, characteristics and advancement in the field of vaccine drug delivery.
Keywords: vaccine, drug delivery, needle free delivery, intradermal, intranasal, transcutaneous